The Comfort of the Mystics: A Manual and Anthology of Early Sufism By Gerhard Böwering and Bilal Orfali (Leiden: Brill, 2013. 34 (English) + 686 (Arabic) pages.) (American Journal of Islam and Society, 2014)
The early period of Sufism still remains insufficiently explored within westernscholarship. Despite the contributions of a range of academic authorities overthe past two centuries, stretching back to the publication of Lt. Graham’s 1819essay, “A Treatise on Sufism, or Mahomedan Mysticism,” followed by the firstmajor European study of the subject two years later by the young Friedrich A.Tholuck, Ssufismus, sive Theosophia Persarum Pantheistica (Sufism, or thePantheistic Theosophy of the Persians), there still remains a great deal of workto be done in order to better understand the complex, embryonic stages of theIslamic mystical tradition. In this light, The Comfort of the Mystics is a welcomecontribution to our growing but still inadequate knowledge of the first few centuriesof taṣawwuf.The present work is a critical edition of Abu Khalaf al-Tabari’s (d. 1077)Salwat al-‘Ārifīn wa Uns al-Mushtāqīn (The Comfort of Those Knowing Godand the Intimacy of Those Longing for God), a Sufi manual authored in themiddle of the eleventh century, shortly after Qushayri’s (d. 1072) famousRisālah. Gerhard Böwering and Bilal Orfali are to be credited with publishingthe Salwat for the first time through a close study of the Cairo manuscript(MS Tal‘at Tasawwuf 1553) which was transcribed a decade before Qushayri’sdeath. While they were unable to access the only other existing manuscript ofthe entire version of the Salwat, located in Iraq, due no doubt to the politicalinstability of the region and the post-war destruction of the country’s infrastructure,they did manage to compare the work against two later abridgedversions. Along with the text, they provide a meticulously referenced introductionwhich situates the treatise within its broader historical and religiouscontext. The Arabic text is also accompanied by exhaustive indices (127pages) for Qur’anic verses, hadiths, key figures, locations, technical terms andpoetic verses which will be of particular use for researchers.With respect to the author of this little known work, Böwering and Orfalinote that the primary sources do not provide us with a great deal of informationabout his life. On the basis of a well-researched analysis of the medievalsource material, they conclude that Tabari was known for his contributionsnot to the field of Sufism but Shafi‘i law, having studied under some of theleading representatives of the school, including ‘Abd al-Qahir al-Baghdadi(d. 1038), well known for his Al-Farq Bayn al-Firaq, a heresiological survey ...